2011
DOI: 10.1016/j.antiviral.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Interference of ribosomal frameshifting by antisense peptide nucleic acids suppresses SARS coronavirus replication

Abstract: The programmed −1 ribosomal frameshifting (−1 PRF) utilized by eukaryotic RNA viruses plays a crucial role for the controlled, limited synthesis of viral RNA replicase polyproteins required for genome replication. The viral RNA replicase polyproteins of severe acute respiratory syndrome coronavirus (SARS-CoV) are encoded by the two overlapping open reading frames 1a and 1b, which are connected by a −1 PRF signal. We evaluated the antiviral effects of antisense peptide nucleic acids (PNAs) targeting a highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 55 publications
3
92
0
Order By: Relevance
“…This issue is however far from being concluded. Ahn et al evaluated the antiviral effects of antisense PNAs targeting a highly conserved RNA sequence on the programmed-1 ribosomal frameshifting signal [122]. The ribosomal frameshifting was inhibited by the PNA without induction of type I interferon responses, suggesting that the effect of PNA is not due to innate immune responses [122].…”
Section: Future Perspectivementioning
confidence: 98%
“…This issue is however far from being concluded. Ahn et al evaluated the antiviral effects of antisense PNAs targeting a highly conserved RNA sequence on the programmed-1 ribosomal frameshifting signal [122]. The ribosomal frameshifting was inhibited by the PNA without induction of type I interferon responses, suggesting that the effect of PNA is not due to innate immune responses [122].…”
Section: Future Perspectivementioning
confidence: 98%
“…Another interesting result was produced by Chaubey et al, who described that a Transportan-PNA molecule, which had previously been shown to display signifi cant antiviral effi ciency (14a), is also a potent virucidal agent, rendering HIV-1 virions pre-treated with the conjugate noninfectious, suggesting a probable prophylactic medical application for their molecule [ 129 ]. PNA-CPPs such as the Tat-FS can also be used to block the frameshift process required for the replication of such viruses as SARS-Coronavirus, making them a viable tool against any viruses that require frameshifting to take place during their replication [ 130 ]. A successful Tat-based application of PNAs has been shown to lead to Japanese encephalitis virus inhibition by competing with RdRp through interactions with its binding sites at 3′ regions of the RNA [ 131 ].…”
Section: Application Of Amps As Drug Delivery Vectorsmentioning
confidence: 98%
“…This suggests that disruption of translation initiation is more effective than an RNAi target within the ORF at limiting viral propagation. Even so, PNAs targeting the pseudoknot caused a significant reduction in the replication of a SARS replicon at concentrations in the low μM range validating the selection of the pseudoknot as an antiviral target (Ahn et al, 2011).…”
Section: Targeting Coronavirus Frameshift Signalsmentioning
confidence: 99%
“…The complexities of coronaviral replication are still being unravelled but it is apparent that www.intechopen.com Viral Genomes -Molecular Structure, Diversity, Gene Expression Mechanisms and Host-Virus Interactions 96 frameshifting is essential for the production of the proteins involved. Altering frameshifting efficiency has been shown to be detrimental for coronavirus replication (Ahn et al, 2011;McDonagh et al, 2011;Plant et al, 2010).…”
Section: Frameshift Signals In the Order Nidoviralesmentioning
confidence: 99%
See 1 more Smart Citation